Stunting Prevention is Alan Effort to Reduce the Risk of Stunting - Dini Afriani; Shinta Amelia Febriani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their body length or height being below standard. Stunting is a condition of growth failure in children (body and brain growth) due to malnutrition for a long time. So the child is shorter than normal children his age and has delays in thinking. Malnutrition lasts for a long time from the time the fetus is in the womb until the beginning of the child's life (the first 1000 days of birth). In Sundamekar Village, Cisitu District, Sumedang Regency in 2022 there were 12 people and in 2023 the stunting rate in Sundamekar Village decreased to 11 people. Implementation of community service Keywords: Stunting, nutrition, children, and knowledge of mother. This aims to help mothers increase their knowledge and awareness of how important it is to prevent stunting and provide an understanding that stunting is not a disease that can be transmitted. This community service activity was carried out on February 1 2024. The focus of this community service activity is to increase the knowledge of mothers in Sundamekar Village regarding stunting in an effort to prevent stunting from pregnancy, children from birth to 5 years of age. The target of community service activities is pregnant women, breastfeeding mothers and mothers of toddlers. Counseling is carried out offline, covering the definition of stunting, causes of stunting, symptoms of stunting, main targets of stunting, parenting patterns, how to prevent stunting and prevent stunting with balanced nutrition. This activity ran smoothly and interactively and the mothers were very enthusiastic about listening to the counseling process.